An examination of how fielding outcomes in international and franchise T20 and 50-over cricket are associated with bowling performances and field positions - Jamil, M.; Manthorpe, S.; MacDonald, D.; Ez-Zizi, A. (International Journal of Performance Analysis in Sport, 2026)
In this study, 4,660 fielding outcomes from international 50-over and T20 cricket as well as multiple international franchise T20 leagues between 2016 and 2020 were examined. A generalised linear model was applied and the results revealed that infielders are less likely to drop catches than outfielders. Furthermore, outfielders in front of square are most likely to drop catches. In addition, drop catches are more likely to occur from spin bowling rather than fast bowling and interestingly, the odds of dropping a catch are lower when bowling a leg-side line. With regards to mis-fields, infielders are revealed to be less likely to mis-field than outfielders. Furthermore, mis-fields are more likely to occur from spin bowling rather than fast bowling. Run-outs were discovered to be more likely to occur in deep fielding positions on the leg-side, less likely to occur during powerplay overs and more likely to occur when bowlers bowl leg-side lines. Stumpings were revealed in this study to be significantly less likely when bowling a leg-side line. From a practical perspective, these findings can offer some assistance to team captains when positioning fielders as well as guide coaching practice.